Cognitive Behaviour Therapy untuk Mengurangi Prokrastinasi Akademik Siswa: Literature review - Ayuna, Rihya Syifa Qurrotu; Wahyuni, Eka (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2023)
CBT views academic procrastination as caused by a distortion cognitive of irrational thinking which assumes that homework are something that is difficult to complete and not easy to do. CBT theory states that students who procrastinate result in their solid cognitive structure and CBT works by replacing dysfunctional thoughts with rational ones. The three structures in cognitive behavior are: Automatic Thinking, Intermediate Beliefs, Core Beliefs. CBT focuses on changing dysfunctional thinking and behavior patterns so that CBT's tasks and commitments fit theoretically into Academic Procrastination. CBT provides appropriate interventions, such as value-directed behavior and goal setting (values), behavioral modeling and experiments (expectations), sub-goals and behavioral activation (time), as well as stimulus and implementation sensitivity to academic procrastination. The results of the study revealed that CBT was very effective in reducing students' academic procrastination. Although effective, CBT has some drawbacks because CBT interventions are relatively expensive and require a high level of expertise.